Sistemas de identificação biométrica: a propósito do controlo. - José Augusto Simões (Acta Médica Portuguesa, 2011)
The ethics and morals make the line between lawful to unlawful, the right and wrong, acceptable from the unacceptable. Furthermore the purpose of ethics in the field of profesional practice is, in particular the application of moral standards based on honesty, courtesy and honour. But they are not the only ones. Confidentiality should be the first of duties the professional has no right to disclose information that was only reported in their work and because it was necessary to run it. This requirement aims to protect the recipient of the service and avoid damage to society. The professional should also encourage members of his team, because solidarity is a very effective way to improve the intellectual and moral qualities of work partners and ensure their involvement. When you have an honest professional conduct within and outside of professional practice, you attract confidence and prestige, which is an incentive to drive, with safety, the proper course of his career. The purpose of the biometric control based on the need to expedite the fulfilment of a goal whose integration is recognized by law under the control of the employer's: the setting of working hours, monitoring the attendance and registration of working time. This record is also the accounting and control of additional work. To consider the biometric control as an appropriate mean to ensure a «legitimate purpose», the Law 67/98 requires the National Commission for Data Protection, in each case, to ascertain whether the prevailing interests the rights and freedoms guarantees data subjects on the interest for the treatment of data relied upon by the employer. This procedure seems to be the best fit to the principle of proportionality and therefore the processing of data should be refused where it appears unjustified, inappropriate and excessive, or when, by their lack of reliability, it undermines the purpose of determining it.